Pengaruh People dan Physical Evidence terhadap Kepuasan Pasien Rawat Inap pada RSUD Ahmad Ripin Muaro Jambi - Riko Mappadeceng; Fadil Iskandar; Delia Rustiela (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Hospitals have a very strategic role in the effort to accelerate the improvement of human health status. Health problems have become a basic need for the community, several empirical studies on people's satisfaction and physical evidence give inconsistent results where some studies show that people and physical evidence have no significant effect on satisfaction, but on the other hand there are also studies that show different things. Based on this explanation, the researcher is interested in submitting the research title "the influence of people and physical evidence on the satisfaction of inpatients at the Ahmad Ripin Hospital, Kab. Muaro Jambi. The purpose of this study was to determine the effect of people and physical evidence on inpatient satisfaction at Ahmad Ripin Hospital, Muaro Jambi Regency. The object of this study was hospitalized patients, while the variables studied were related to the community and physical evidence of patient satisfaction. The population in this study were inpatients at RSUD Ahmad Ripin Kab. Muaro Jambi with a total sample of 89 people. The data analysis technique used is multiple linear regression, classical assumption test and hypothesis testing.The results showed that people did not have a significant positive effect on satisfaction at Ahmad Ripin Hospital, Muaro Jambi Regency, while physical evidence had a significant positive effect on satisfaction at Ahmad Ripin Hospital, Muaro Jambi Regency.